Mapping of Chronic Pulmonary Aspergillosis in Africa - Olum, Ronald; Osaigbovo, Iriagbonse Iyabo; Baluku, Joseph Baruch; Stemler, Jannik; Kwizera, Richard; Bongomin, Felix (Journal of Fungi, 2021)
Africa has a high burden of tuberculosis, which is the most important risk factor for chronic pulmonary aspergillosis (CPA). Our goal was to systematically evaluate the burden of CPA in Africa and map it by country. We conducted an extensive literature search for publications on CPA in Africa using the online databases. We reviewed a total of 41 studies published between 1976 and 2021, including a total of 1247 CPA cases from 14 African countries. Most of the cases came from Morocco (n = 764, 62.3%), followed by South Africa (n = 122, 9.9%) and Senegal (n = 99, 8.1%). Seventeen (41.5%) studies were retrospective, 12 (29.3%) were case reports, 5 case series (12.2%), 5 prospective cohorts, and 2 cross-sectional studies. The majority of the cases (67.1%, n = 645) were diagnosed in men, with a median age of 41 years (interquartile range: 36–45). Active/previously treated pulmonary tuberculosis (n = 764, 61.3%), human immunodeficiency virus infection (n = 29, 2.3%), diabetes mellitus (n = 19, 1.5%), and chronic obstructive pulmonary disease (n = 10, 0.8%) were the common co-morbidities. Haemoptysis was the most frequent presenting symptom, reported in up to 717 (57%) cases. Smoking (n = 69, 5.5%), recurrent lung infections (n = 41, 3%) and bronchorrhea (n = 33, 3%) were noted. This study confirms that CPA is common in Africa, with pulmonary tuberculosis being the most important risk factor.
Keywords: chronic pulmonary aspergillosis; Aspergillus; tuberculosis; Africa